2011
DOI: 10.1007/s10072-011-0622-4
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of endothelial-derived relaxing factors in the regulation of cerebral blood flow

Abstract: Despite numerous researches and advances in the present times, delayed cerebral vasospasm remains a severe complication leading to a high mortality and morbidity in patients with subarachnoid hemorrhage (SAH). Since the discovery of endothelium-derived relaxing factor (EDRF) in 1980, its role in delayed cerebral vasospasm after SAH has been widely investigated as well as in regulation of basic cerebral blood flow, pathophysiology of vasoconstriction and application on prevention and treatment of cerebral vasos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…The first identified gasotransmitter molecule in the mammalian circulation was NO [16] which was shown to increase cerebral blood flow by decreasing vascular resistance in the cerebral vessels similarly to its effects in the systemic circulation [17]. NO in the central nervous system may originate from endothelial cells (produced by endothelial NOS, eNOS), from autonomic nitrergic nerve endings or from neurons of the central nervous system (produced by neuronal nitric oxide synthase, nNOS), or by the inducible isoform of the enzyme (iNOS) [17,18]. Decreased availability of NO is known to be a triggering factor of vasospasm after subarachnoid hemorrhage, whereas overproduction through iNOS occurs during inflammation or cerebral ischemia [18].…”
Section: Gasotransmitters In Cerebral Circulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The first identified gasotransmitter molecule in the mammalian circulation was NO [16] which was shown to increase cerebral blood flow by decreasing vascular resistance in the cerebral vessels similarly to its effects in the systemic circulation [17]. NO in the central nervous system may originate from endothelial cells (produced by endothelial NOS, eNOS), from autonomic nitrergic nerve endings or from neurons of the central nervous system (produced by neuronal nitric oxide synthase, nNOS), or by the inducible isoform of the enzyme (iNOS) [17,18]. Decreased availability of NO is known to be a triggering factor of vasospasm after subarachnoid hemorrhage, whereas overproduction through iNOS occurs during inflammation or cerebral ischemia [18].…”
Section: Gasotransmitters In Cerebral Circulationmentioning
confidence: 99%
“…NO in the central nervous system may originate from endothelial cells (produced by endothelial NOS, eNOS), from autonomic nitrergic nerve endings or from neurons of the central nervous system (produced by neuronal nitric oxide synthase, nNOS), or by the inducible isoform of the enzyme (iNOS) [17,18]. Decreased availability of NO is known to be a triggering factor of vasospasm after subarachnoid hemorrhage, whereas overproduction through iNOS occurs during inflammation or cerebral ischemia [18]. Several evidences provided by experiments involving animals indicate that the NOS enzyme contributes to the neurovascular coupling (known as functional hyperemia) and a recent study demonstrated this in humans as well [15,19].…”
Section: Gasotransmitters In Cerebral Circulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important mechanism regulating vascular tone is the production of endothelium-derived relaxing factors (EDRFs), where blood vessels, particularly arteries, can produce relaxation in response to blood flow, shear stress and circulatory vasodilators, which may importantly contribute to the control of vascular tone under physiological or pathological conditions (Edwards et al, 2010; Qi et al, 2011; Vanhoutte et al, 2009). It is well known that Ca 2+ activation of ECs is critically implicated in the production of EDRFs such as nitric oxide (NO), epoxyeicosatrienoic acids (EETs) and prostacyclins (Yi et al, 2002; Zhang et al, 2005; Zhang et al, 2004).…”
Section: Functional Relevance Of Cadpr or Naadp-mediated Signalingmentioning
confidence: 99%
“…8 These and other aspects of normal cerebral vascular function are described in detail in numerous reviews. [9][10][11][12][13][14][15][16] Traumatic brain injury (TBI) impairs or abolishes many cerebral vascular compensatory responses in humans and experimental animals. 9,[17][18][19] Increased vulnerability to secondary insults may be due, in part, to traumatic cerebral vascular injury resulting in impaired compensatory responses to changes in levels of arterial blood pressure, carbon dioxide, oxygen, and so on.…”
Section: Introductionmentioning
confidence: 99%